(untitled) (Bangladesh Journal of Medical Science, 2025)
The presented technique highlights the remote color evaluation of skin and an auricular maxillofacial prosthesis using color-corrected images facilitated by a custom 18% middle-grey virtual background in a teleconferencing software application. The International Commission on Illumination (CIE) introduced L, a* and b* color values were extracted from images using a photo editing software and plotted within an equation to evaluate the Euclidean color differences (ΔE) at different times of the day where the L, a* and b* values from the healthy ear images were considered as standard. Consistent ΔE color differences were produced and there were no significant differences in L, a* and b* color coordinates when compared statistically to professional color calibration tools. The presented technique is a viable, cost-effective alternative for evaluating color changes of auricular prostheses that can be used to guide the need for replacement utilizing a teledentistry platform. Bangladesh Journal of Medical Science Vol. 24 No. 02 April’25 Page : 406-412